Insulin is a potent myeloma cell growth factor through insulin/IGF-1 hybrid receptor activation - Sprynski, A. C.; Hose, Dirk; Kassambara, A.; Vincent, L.; Jourdan, M.; Rossi, J. F.; Goldschmidt, Hartmut; Klein, B. (Leukemia, 2010)
Insulin and insulin growth factor type 1 (IGF-1) and their receptors are closely related molecules, but both factors bind to the receptor of the other one with a weak affinity. No study has presently documented a role of insulin as a myeloma growth factor (MGF) for human multiple myeloma cells (MMCs), whereas many studies have concluded that IGF-1 is a major MGF. IGF-1 receptor (IGF-1R) is aberrantly expressed by MMCs in association with a poor prognosis. In this study we show that insulin receptor (INSR) is increased throughout normal plasma cell differentiation. INSR gene is also expressed by MMCs of 203/206 newly diagnosed patients. Insulin is an MGF as potent as IGF-1 at physiological concentrations and requires the presence of insulin/IGF-1 hybrid receptors, stimulating INSR+IGF-1R+ MMCs, unlike INSR+IGF-1R− or INSR−IGF-1R− MMCs. Immunoprecipitation experiments indicate that INSR is linked with IGF-1R in MMCs and that insulin induces both IGF-1R and INSR phosphorylations and vice versa. In conclusion, we demonstrate for the first time that insulin is an MGF as potent as IGF-1 at physiological concentrations and its activity necessitates insulin/IGF-1 hybrid receptor activation. Further therapeutic strategies targeting the IGF/IGF-1R pathway have to take into account neutralizing the IGF-1R-mediated insulin MGF activity.